RNA editing of the 5-HT(2C) receptor is reduced in schizophrenia. - Sodhi, MS; Burnet, P; Makoff, A; Kerwin, R; Harrison, P (2001)
5-HT(2C) receptor (5HT(2C)R, serotonin-2C) RNA undergoes editing to produce several receptor variants, some with pharmacological differences. This investigation comprised two parts: the characterisation of 5-HT(2C)R RNA editing in a larger human control sample than previously examined, and a comparative study in subjects with schizophrenia. Secondary structure analysis of the putative edited region of the human 5-HT(2C)R gene predicted the existence of a double stranded (ds) RNA loop, essential for RNA editing in this receptor. RNA was then extracted from frontal cortex of five controls and five subjects with schizophrenia. RT-PCR products of the edited region were cloned and sequenced (n = 100). Reduced RNA editing, increased expression of the unedited 5-HT(2C-INI) isoform in schizophrenia (P = 0.001) and decreased expression of the 5-HT(2C-VSV) and 5-HT(2C-VNV) isoforms were detected in the schizophrenia group. In addition, two novel mRNA edited variants were identified: 5-HT(2C-MNI) and 5-HT(2C-VDI). Screening of the 5-HT(2C)R gene did not reveal any mutations likely to disrupt the dsRNA loop, suggesting that the reduced RNA editing in schizophrenia may instead be caused by altered activity of the editing enzyme(s). Since the unedited 5-HT(2C-INI) is more efficiently coupled to G proteins than the other isoforms, its increased expression in schizophrenia may lead to enhanced 5-HT(2C)R-mediated effects. The results also illustrate that potentially important receptor alterations may occur in schizophrenia which are not detectable merely in terms of receptor abundance.